ISOLASI DAN PENGKLONAN FRAGMEN cDNA DARI GEN PENYANDI MULTIDRUG RESISTANCE ASSOCIATED PROTEIN DARI Melastoma affine - Suharsono, Suharsono; Firdaus, Syarifin; Suharsono, Utut Widyastuti (UI Scholars Hub, 2008)
Isolation and Cloning of cDNA Fragment of Gene Encoding for Multidrug Resistance Associated Protein from M. affine. M. affine can grow well in acid soil with high level of soluble aluminum. One of the important proteins in the detoxifying xenobiotic stress including acid and Al stresses is a multidrug resistance associated protein (MRP) encoded by mrp gene. The objective of this research is to isolate and clone the cDNA fragment of MaMrp encoding MRP from M. affine. By reverse transcription, total cDNA had been synthesized from the total RNA as template. The fragment of cDNA MaMrp had been successfully isolated by PCR by using total cDNA as template and mrp primer designed from A. thaliana, yeast, and human. This fragment was successfully inserted into pGEM-T Easy and the recombinant plasmid was successfully introduced into E. coli DH5α. Nucleotide sequence analysis showed that the lenght of MaMrp fragment is 633 bp encoding 208 amino acids. Local alignment analysis based on nucleotide of mRNA showed that MaMrp fragment is 69% identical to AtMrp1 and 63% to AtMrp from A. thaliana. Based on deduced amino acid sequence, MaMRP is 84% identical to part of AtMRP13, 77% to AtMRP12, and 73% to AtMRP1 from A. thaliana respectively. Alignment analysis with AtMRP1 showed that MaMRP fragment is located in TM1 and NBF1 domains and has a specific amino acid sequence QCKAQLQNMEEE